Assessment of income growth in patients with rheumatoid arthritis treated with anti-tumor necrosis factor therapy. (January 2015) - Bergman, Martin; De, Gourab; Ganguli, Arijit; Signorovitch, James; Bao, Yanjun
Abstract Objectives: To compare income growth over time between employees with RA treated with anti-TNFs and those treated with methotrexate (MTX). Methods: Privately insured employees (aged ≥18) with ≥1 RA diagnosis (ICD-9: 714.0) were identified from a large-scale US employer claims database (1998–2011). Patients were stratified into treatment groups (anti-TNF-treated patients and MTX-monotherapy patients) based on their treatment history. The anti-TNF-treated patients comprised patients who filled ≥1 prescription for anti-TNFs, with or without MTX (index date defined as the date of the first anti-TNF prescription). The MTX-treated patients comprised patients who filled ≥1 prescription for MTX-monotherapy (index date randomly selected). The primary study outcome was the annual income growth rate (US dollars). Patients were followed from their index date to health plan disenrollment or the end of data availability (maximum follow-up of 5 years). The effect of treatment type on income growth was assessed using a multivariable generalized estimating equation model, adjusting for key baseline characteristics. Income growth was compared to that of the general employed population using Social Security data (1998–2011). Results: The regression-adjusted annual growth rate in income for anti-TNF-treated patients (n = 1848) was 2.8% (CI = 1.9–3.6%), significantly greater (p < 0.05) than the 0.6% (CI = −0.2–1.4%) for MTX-monotherapy patients (n = 1866). Compared to the general employed population, income growth was lower (p < 0.05) for MTX-monotherapy patients and comparable for anti-TNF-treated patients. Conclusions: Compared to MTX-monotherapy, anti-TNF treatment is associated with a higher income growth rate among employees with RA. Anti-TNF-treated patients experienced comparable income growth to the general employed population norm.